The CGIAR Initiative on Low-Emission Food Systems (Mitigate+): Economic Modelling for Green Aquatic Food Systems - Le, Quyen; Huong, Le; Chan, Chin Yee (VIEP, 2024)
Tthe Consultative Group on International Agricultural Research (CGIAR)’s Initiative on Low-Emission Food Systems (MITIGATE+) sponsored a training course in Vietnam from 14 to 16 December 2022 in Hanoi. The training course covers various topics in applied economics, including partial equilibrium and general equilibrium models. The course emphasizes research and application tools in fishery economics and applied quantitative policy analysis. Applications encompass constructing marginal abatement cost curves (MACCs), conducting preference and welfare analysis, exploring local and general equilibrium concepts, and managing open fisheries resources. In addition to paper-based practical exercises, participants in the course utilized computers for policy assessments and analysis, engaging in in-depth discussions that combined theoretical knowledge, practical skills, and the real-world investigative experience of Vietnamese researchers.